2006
DOI: 10.4067/s0717-95022006000400028
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and Somatic Development: Application of Protocol of Mensuration to Evaluation of Indicators of Wistar Rats

Abstract: This study analyzed the consequence of malnutrition and/or serotoninergic manipulation during the period of fast growth of encephalon on the somatic development in rats. It was used the protocol of measurement of indicators of this development proposed by Silva et al., 2005. The protocol was applied from 1st to 21st day and rats were breastfed by female which received control diet (commercial diet, Labina) with 23% of protein, normoproteic diet, nourished animals (Group Nourished-Nour), n=15 or were breastfed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…23,[25][26][27] In the present study, the association between malnutrition and dental crowding was found only after the variable pacifier use was identified as being effect modifying, which allowed for a more accurate investigation based on the heterogeneity of effect on the population. We found positive association between malnutrition, based on the W/A index, and dental crowding among those children who did not use pacifiers, that is, the habit of using pacifiers serves as a protection against the occurrence of dental crowding among the children with malnutrition.…”
Section: Discussionmentioning
confidence: 94%
“…23,[25][26][27] In the present study, the association between malnutrition and dental crowding was found only after the variable pacifier use was identified as being effect modifying, which allowed for a more accurate investigation based on the heterogeneity of effect on the population. We found positive association between malnutrition, based on the W/A index, and dental crowding among those children who did not use pacifiers, that is, the habit of using pacifiers serves as a protection against the occurrence of dental crowding among the children with malnutrition.…”
Section: Discussionmentioning
confidence: 94%